Analisis Data Investasi, Pengeluaran Pemerintah, Dan Pertumbuhan Ekonomi Di Sulawesi Selatan Tahun 2020–2024 - Suhardi, Wisda Zulaeha (STIM-LPI Makassar, 2025)
This study aims to analyze the relationship between private investment, government spending, and economic growth in South Sulawesi Province from 2019 to 2023. The background of this study is based on the general assumption that increased investment and government spending play a significant role in driving regional economic growth. This study uses a descriptive quantitative approach with secondary data obtained from official government sources. The analysis was conducted using descriptive statistics and Pearson correlation tests to determine the extent of the relationship between variables. The results show no significant relationship between private investment and economic growth, nor between government spending and economic growth. Although there is a trend of increasing investment and government spending, this is not directly reflected in changes in the rate of economic growth in the region. These findings indicate that the effectiveness of fiscal and investment policies in the region is highly dependent on the quality of implementation, infrastructure readiness, and cross-sector synergy. Therefore, a policy strategy is needed that focuses not only on the size of the budget or investment value, but also on optimizing its impact on sustainable economic growth.